2007
DOI: 10.1021/ja069148u
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Protein Assembly as Scaffold for Time-Resolved Fluoroimmuno Assays

Abstract: Turnip yellow mosaic virus (TYMV) is an icosahedral plant virus with an average diameter of 28 nm and can be isolated in gram quantities from turnip or Chinese cabbage inexpensively. In this study, it was selected as a prototype bionanoparticle for time-resolved fluoroimmuno assay (TRFIA). Two types of reactive amino acid residues were employed to anchor luminescent terbium complexes and biotin groups based on orthogonal chemical reactions. While terbium complexes were used as luminescent signaling groups, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 69 publications
0
55
0
Order By: Relevance
“…ESI HRMS spectra for compounds were recorded using Micromass Q-TOF. TYMV was purified from infected Chinese cabbage leaves following the procedure as described [43]. Chemical modification of TYMV with the desired compounds and its characterization was done using the established protocols as described [42].…”
Section: General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ESI HRMS spectra for compounds were recorded using Micromass Q-TOF. TYMV was purified from infected Chinese cabbage leaves following the procedure as described [43]. Chemical modification of TYMV with the desired compounds and its characterization was done using the established protocols as described [42].…”
Section: General Methodsmentioning
confidence: 99%
“…N-(propargyl)-2-methylbenzothiazolium bromide 1 was synthesized according to a known protocol [41]. Protein gel and Western blotting were performed on a 15% SDS-PAGE gel following the standard protocols [43]. The primary TYMV polyclonal antibody was provided by Prof. Theo Dreher (Oregon State University).…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The systematic characterization of cowpea mosaic virus (CPMV) [40 44], along with studies of cowpea chlorotic mottle virus (CCMV) [45], bacteriophage MS2 [46], heat shock protein [18], tobacco mosaic virus (TMV) [47], and turnip yellow mosaic virus (TYMV) [48], have shed light on the unique chemical reactivities and physical properties of these individual BNPs. These initial discoveries have been integred to design BNPs as nano-scaffolds for drug delivery, bioimaging, biomineralization, and even tissue engineering.…”
Section: Chemically Addressable Bionanoparticlesmentioning
confidence: 99%
“…These reagents have been previously used in the derivatization of carboxylic groups of ferritins with long chain aliphatic amines, resulting in stable, hydrophobic macromolecules [53,54]. In recent years, systematic characterizations implemented with EDC coupling reactions have been conducted on various plant viruses (CPMV, TYMV, CCMV, and TMV) [45,47,48,55]. Schlick and co-authors reported efficient coupling via EDC in the presence of 1-hydroxybenzotriazole (HOBT) [47].…”
Section: Chemically Addressable Bionanoparticlesmentioning
confidence: 99%